ROTIFERS AND OTHER LITTORAL ZOOPLANKTON SPECIES FROM THE ANDEAN LAGOONS OF PACA AND ÑAHUINPUQUIO, JAUJA, JUNIN, PERU - Iannacone, José (2013)
We evaluate rotifers and other littoral zooplankton species of high Andean lagoons (~3400 m) of Paca (75 ° 30'LW, 11 ° 40 ¨ LS) and Ñahuinpuquio (75 ° 32'LW, 11 ° 46'LS), Junin, Peru. In August 1994, were monitored quantitatively rotifers and other zooplankton species from Andean lagoons of Ñahuinpuquio and Paca using a plankton net at 45 um mesh diameter. Values are expressed in N ° org·L-1. In the 16 stations, Paca lagoon were recorded a total of 22 species, an average of six species (0-12), 30 org·L-1 (0-164) and a value of Shannon-Wiener index of 2.11 bits·ind-1. Registered rotifers were Keratella cochlearis (Gosse, 1851) (37.5% of the stations) and Rotaria sp. (12.5% of the stations). In the 17 stations, in Ñahuinpuquio lagoon we recorded a total of 34 species, an average of 12 species (0-27), 22 org·L-1 (0-53) and a value of Shannon-Wiener index 2.95 bit·ind-1. The rotifers found were: K. cochlearis (58.88% of the stations), Rotaria sp. (5.88% of the stations), Platyas quadricornis Harring, 1913 (5.88% of the stations) and Trichocerca sp. (5.88% of the stations). Beta diversity using the similarity index of Jaccard qualitative (I ) and the J quantitative Bray-Curtis (I ) reported for zooplankton values for Ñahuinpuquio and Paca, 50% B-C and 59.7%, respectively. Estimates of the number of zooplankton species to Paca and Ñahuinpuquio lagoons were as Chao-1 (22.5, 52), Jacknife-1 (22, 50) and Bootstrap (22, 45), respectively.